The Mid-Infrared Instrument for the James Webb Space Telescope, III: MIRIM, The MIRI Imager. (4th January 2016) - Bouchet, Patrice; García-Marín, Macarena; Lagage, P.-O.; Amiaux, Jérome; Auguéres, J.-L.; Bauwens, Eva; Blommaert, J. A. D. L.; Chen, C. H.; Detre, Ö. H.; Dicken, Dan; Dubreuil, D.; Galdemard, Ph.; et al.
Abstract: In this article, we describe the Mid-Infrared Imager Module (MIRIM), which provides broadband imaging in the 5-27 μm wavelength range for the James Webb Space Telescope . The imager has a$0\overset{''}{.}11$ pixel scale and a total unobstructed view of 74″ × 113″. The remainder of its nominal 113″ × 113″ field is occupied by the coronagraphs and the low-resolution spectrometer. We present the instrument optical and mechanical design. We show that the test data, as measured during the test campaigns undertaken at CEA-Saclay, at the Rutherford Appleton Laboratory, and at the NASA Goddard Space Flight Center, indicate that the instrument complies with its design requirements and goals. We also discuss the operational requirements (multiple dithers and exposures) needed for optimal scientific utilization of the MIRIM.